2012
DOI: 10.3892/ijo.2012.1673
|View full text |Cite
|
Sign up to set email alerts
|

T-box transcription factor Brachyury expression is correlated with epithelial-mesenchymal transition and lymph node metastasis in oral squamous cell carcinoma

Abstract: The prognosis of patients with oral squamous cell carcinoma (SCC) is influenced by the presence of lymph node metastasis. Epithelial-mesenchymal transition (EMT), a process that involves events that convert adherent epithelial cells into individual migratory cells that can invade the extracellular matrix, is critical for cancer progression. Recently, the T-box transcription factor Brachyury was reported to promote EMT in human carcinoma cell lines. We analyzed the relationship between EMT (assessed by staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 35 publications
4
40
0
Order By: Relevance
“…These results are consistent with those of previous studies, which revealed that silencing brachyury expression inhibits tumor formation and metastasis in human adenoid cystic carcinoma cells (19,20). In addition, a previous study revealed that brachyury expression is associated with EMT and lymph node metastasis in OSCC patients (22).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with those of previous studies, which revealed that silencing brachyury expression inhibits tumor formation and metastasis in human adenoid cystic carcinoma cells (19,20). In addition, a previous study revealed that brachyury expression is associated with EMT and lymph node metastasis in OSCC patients (22).…”
Section: Discussionsupporting
confidence: 82%
“…Recently, the T-box transcription factor brachyury, which is essential for mesoderm formation during early development (16,17), has been found to regulate the epithelial-mesenchymal transition (EMT) and CSC potential in human salivary carcinoma cells (18)(19)(20)(21). In addition, brachyury expression was found to correlate with lymph node metastasis in OSCC (22). However, to date, the association between SOX2, Oct4, KLF4, c-Myc and brachyury expression in OSCC has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that Brachyury was highly expressed in human tumor cells, but not in the corresponding normal cell lines (29). Fernando et al reported that Brachyury could induce EMT in human epithelial cells through the repression of E-cadherin and the induction of Slug (31).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, during the EMT process, cells may lose epithelial markers and adherent ability, and gain mesenchymal markers and invasive capability, which can convert normal cells into tumor cells, contributing to the metastasis and invasiveness of the tumor (29). Hence, the relationship between EMT and TNBC needs to be urgently investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation